Self-concept of high school students with various levels of mathematical giftedness - Rovan, Daria; Vlahović-Štetić, Vesna (2008)
The aim of this study was to explore the effect of level of mathematical giftedness and gender on students' self-concept (represented by personal competence perceptions, fear of negative evaluation and self-esteem), while controlling for their general school achievement. Participants in the study were high school students forming three groups: highly gifted (N=62), moderately gifted (N=99) and non-gifted students (N=77). Mathematically gifted students did not differ from their non-gifted peers in their personal competence, fear of negative evaluation and their self-esteem evaluations. The effect of gender was significant only for the fear of negative evaluation indicating that female student show more intensive fear than their male peers. For the measure of self-esteem significant interaction between gender and mathematical giftedness level was found. For the male students the highest self-esteem estimates were in the highly gifted students group and the lowest in moderately gifted students group. Among the girls, moderately gifted girls have the highest self-esteem followed by highly gifted girls and than by non-gifted with the lowest self-esteem.
Projekt MZOS
ENG